Indikasi Manajemen Laba (Earnings Management) dan Hubungannya dengan Kinerja Operasi Disekitar Initial Public Offering (Ipo) pada Perusahaan-Perusahaan Manufaktur yang Terdaftar di Bursa Efek Jakarta - Sri Anik (Journal of Accounting and Investment, 2004)
The objective of this study is to found empirical about manufacture companies which the listed in Jakarta Stock Exchange performed the earnings management surrounding Initial Public Offering and association between Initial Public offering. The research variables which are examined in this study: earnings management with indicator Discretionary Acrual (DA) and operating performance with indicator Return on Asset (ROA). The test result shows from 32 manufacture companies performed IPO during 1995-2000, in fact 26 companies were detected commited earnings management, and only 6 companies which were being able to be detected performed earnings management. And the different test result shows that operating performance before IPO and operating performance after IPO relative same, although mean operating performance before IPO bigger from mean operating performance after IPO. The result of this research also shows that association between earnings management with operating performance surrounding IPO are negative association and significant.